An unusual case of thoracic empyema caused by Granulicatella elegans (nutritionally variant streptococci) in a patient with pulmonary tuberculosis and human immunodeficiency virus infection. Issue 5 (September 2016) - Mvelase, Nomonde R.; Marajh, Kanitha; Hattingh, Olga; Mlisana, Koleka P.
Abstract : Introduction: Nutritionally variant streptococci (NVS) are an infrequent cause of human infection with Granulicatella elegans being the least encountered species in clinical specimens. The most common infection caused by NVS is infective endocarditis. Case Presentation: We report an unusual case of thoracic empyema due to G. elegans in a patient with pulmonary tuberculosis (TB) and human immunodeficiency virus infection. The patient responded favourably to drainage and penicillin. Conclusion: This case illustrates that even though TB is responsible for the majority of pleural effusions in this setting, other rare opportunistic bacteria may cause infection in susceptible patients. Therefore, microbiological investigations should be performed in all patients presenting with pleural effusion.